SUSTAINABLE AGRICULTURAL DEVELOPMENT: INNOVATIONS AND STRATEGIES FOR FOOD SECURITY - Rochman, Abdul (CV. Lafadz Jaya, 2025)
Sustainable agricultural development is essential for achieving global food security, especially in developing countries where the majority of the population relies on agriculture for their livelihoods. This paper explores the critical role of innovation, technology adoption, and sustainable practices in enhancing agricultural productivity and resilience against climate change. Through a comprehensive review of the current literature, this research identifies key factors driving successful agricultural development, including advancements in agricultural techniques, effective resource management, and supportive policy frameworks. Additionally, this study examines the challenges faced by the agricultural sector, such as land degradation, water scarcity, and market accessibility. The findings highlight the importance of collaborative efforts among stakeholders, including government authorities, private sectors, and local communities, to create an inclusive and resilient agricultural ecosystem. Furthermore, this paper presents case studies illustrating successful agricultural innovations and practices that contribute to sustainable development. The aim is to provide actionable insights and policy recommendations that can help policymakers and practitioners enhance agricultural productivity, improve farmer livelihoods, and ensure food security in an ever-changing global landscape.